Patterns of Prior and Subsequent Neoplasms in Children and Adolescents With Soft Tissue Sarcomas. Issue 5 (July 2020) - Uckunkaya, Oliver; Nöllke, Peter; Hallmen, Erika; Becker, Cornelia; Stegmaier, Sabine; Sparber-Sauer, Monika; Vokuhl, Christian; Koscielniak, Ewa; Hettmer, Simone
Abstract : Background: The occurrence of prior, concurrent and subsequent neoplasms (SN) represents a serious problem in children and adolescents with soft tissue sarcomas. Pathogenic germline variants contribute to the diagnosis of multiple neoplasms in sarcoma survivors. Materials and Methods: The records of 748 children and adolescents, diagnosed with soft tissue sarcomas and registered in trials/registries by the cooperative soft tissue sarcoma (Cooperative Weichteilsarkom Studie) group, were reviewed for the occurrence of SNs. Reference histology review was available for all cases; the presence of oncogenic fusions known at the time of diagnosis was confirmed for fusion-positive (F+) entities. Results: Concurrent or subsequent SNs developed in 13 of 473 survivors of fusion-negative (F−) sarcomas, for an 8-year cumulative SN incidence of 5% in survivors of F− sarcomas. In contrast, only 1 of 278 survivors of F+ sarcoma developed an SN. Twenty of 748 patients with soft tissue sarcomas had a history of prior neoplasms. Six of 14 patients who developed SNs after their index sarcomas met Chompret criteria for Li-Fraumeni syndrome. Nine of 20 patients who had tumors before their index sarcoma diagnosis had neurofibromatosis type 1 or neurofibromatosis type 1 spectrum tumors. Conclusion: Sarcoma phenotype/genotype and the sequence and nature of prior and subsequent neoplasms provide a window into underlying germline genetic susceptibilities in children and adolescents with soft tissue sarcomas. Abstract : Supplemental Digital Content is available in the text.